Use of the kinematic chain in the fencing attacking lunge - Mulloy, F.; Mullineaux, D. R.; Irwin, G. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Proximal to distal sequencing has been demonstrated in a variety of movements as an optimal solution to generating maximal propulsion. This study aimed to identify whether the kinematic chain is used in the fencing attacking lunge. Six novice and four expert fencers completed attacking lunge movements. Kinematic data were captured, and joint angular velocities compared. The expert group demonstrated a proximal to distal sequence in the rear leg which was not as evident in the novices, resulting in a significantly greater ankle extension velocity (564 ± 132 °.s-1 expert versus 273 ± 184 °.s-1 novice; p<0.05). This sequential pattern capitalizes on the design of the human musculoskeletal system, allowing for greater forward sword velocity to be achieved. The kinematic chain of the rear leg has an optimal solution adopted by expert fencers in the attacking lunge skill.